Reply to Comment by Jennings et al. on "Investigating Earth's Formation History Through Copper and Sulfur Metal‐Silicate Partitioning During Core‐Mantle Differentiation". Issue 12 (6th December 2019) - Mahan, B.; Siebert, J.; Badro, J.; Borensztajn, S.; Moynier, F.
Abstract: Recognizing existing materials that can act as proxies for Earth's building blocks, and understanding the accretionary pathway taken during Earth's growth, persist as outstanding issues in need of resolution. In Mahan, Siebert, Blanchard, Badro, et al. (2018, https://doi.org/10.1029/2018JB015991 ), we conducted diamond anvil cell (DAC) Cu metal‐silicate partitioning experiments and coupled these results with a large complement of literature data to characterize Cu metal‐silicate partitioning during Earth's core formation and accretion history. The Comment of Jennings, Wade, and Llovet (2019, https://doi.org/10.1029/2018JB016930 ) contends that secondary X‐ray fluorescence, originating from the Cu holders that experiments are routinely welded to ("lift‐out" grids), compromises the novel Cu partitioning data of Mahan, Siebert, Blanchard, Badro, et al. (2018) beyond utility. To dispel these concerns and further validate our data, we have (i) investigated secondary X‐ray fluorescence effects in a Cu‐free experiment and provided a matrix‐matched data correction, and (ii) rewelded a DAC experiment from a Cu grid to a Mo grid for a comparison of compositional analyses and Cu partitioning results. Secondary fluorescence results, in fact much like the simulated results in Jennings, Wade, and Llovet (2019), indicate that this effect is essentially equal in the metal and silicate phases and therefore has no actual impact on Cu metal‐silicate partition coefficients. Moreover, Cu concentrations and partition coefficients determined using the Mo grid are statistically indistinguishable from that determined using the Cu grid. All results decisively illustrate that while secondary X‐ray fluorescence must be considered where absolute concentrations are the final objective, it has had no meaningful impact on the partitioning data and observations of Mahan, Siebert, Blanchard, Badro, et al. (2018). Key Points: Secondary X‐ray fluorescence from Cu grids impacts metal and silicate measurements equally, nullifying its effect on partition coefficients Cu partitioning results from the same diamond anvil cell experiment welded to either a Cu or Mo grid are statistically indistinguishable While secondary X‐ray fluorescence merits consideration, such effects are wholly inconsequential to the results of Mahan, Siebert, Blanchard, Badro, et al. (2018)